Escala de madurez gonadal del jurel Trachurus murphyi Nichols 1920 - Sánchez, Javier (2013)
This paper describes the macroscopic scale of gonad maturity stages of Jack mackerel Trachurus murphyNichols 1920, validated by microscopic studies, and being used in Peru,. A scale of six maturity stages are identified for females and males, ranging from stage 0 (virgin) to stage V (recovery in females, post-spermiation in males). The gonads of 350 specimens were analyzed. These specimens were collected as part of a pelagic fishery monitoring programme and during pelagic stock assessment surveys between 2006 and 2009. Virgin individuals are classified as stage 0 (virgin), which draws the distinction between (non-reproductive) juveniles and (reproductive) adults in stages I to V. The advantages of using the validated stages of gonad development of Jack mackerel T. murphyiare discussed and are compared to other scales of maturity stages proposed for other species in the same family. The analysis of the microscopic characteristics of the ovaries confirms that Jack mackerel is a batch spawner, which has already been described by other authors.